Wheat straw biochar and its performance in treatment of phenanthrene containing water and microbial remediation of phenanthrene contaminated soil - Ding, Chengcheng; Gan, Yonghai; Luo, Jun; Cui, Yibin (Frontiers in Environmental Science, 2022)
In recent years, biochar has been considered as an effective adsorbent and soil conditioner due to its abundant carbon and high porosity. This study applied a kind of biochar from wheat straw pyrolysis to remediate phenanthrene-contaminated water and soil. The performance of the biochar in the removal of phenanthrene was discussed by liquid phase adsorption and soil incubation experiments. Furthermore, this work explored the enhancement effect of wheat straw biochar on soil microbial numbers and soil properties. The result of liquid phase adsorption indicated, 92.2% of phenanthrene was removed after incubating 0.6 g/L of wheat straw biochar for 4 h. Pseudo-second-order kinetic model (R2 = 0.99823) and Langmuir isotherm model (R2 = 0.99577) described the removal of phenanthrene by wheat straw biochar well. In soil incubation experiment with an initial phenanthrene content of 11.2 mg/kg, 89.1% of phenanthrene was removed at biochar dosage of 12% (w/w, wheat straw biochar / soil) after 30 days of incubation. In addition, the number of soil microorganisms, soil pH and organic matter (SOM) content increased after wheat straw biochar treatment. At the dosage of 12%, soil microbial count increased to 9.8 × 108 CFU/g-soil, soil pH increased by 1.8 units and SOM increased by 8.5 folds. The addition of wheat straw biochar not only improved soil quality, but also reduced the proportion of phenanthrene components, which could provide theoretical support for the resource utilization of agricultural waste.